The Influence of Corporate Social Responsibility (CSR) on Company Financial Performance: Analysis on the Indonesia Stock Exchange (IDX) - Ambarwati, Hanum Cheffi; Leba, Desinta; Hwihanus (MultiTech Publisher, 2024)
This journal article provides a comprehensive overview of Corporate Social Responsibility (CSR) in the global context and specifically in Indonesia. It examines the importance of integrating CSR into business strategy, highlighting its role in enhancing reputation, stakeholder trust, and long-term sustainability. Furthermore, the discussion explores the relationship between CSR integration and company performance, showcasing how CSR practices can drive financial success and market competitiveness both globally and in Indonesia. Despite facing challenges such as limited awareness and regulatory gaps, Indonesia presents significant opportunities for the advancement of CSR, driven by growing consumer demand for ethical products and services and the country's rich cultural diversity. Looking ahead, the future of CSR in Indonesia holds promise for growth and innovation, with businesses increasingly recognizing CSR as a strategic imperative for creating value and driving positive social and environmental impact. Through addressing challenges, leveraging opportunities, and fostering collaboration among stakeholders, Indonesia can pave the way for a more sustainable and responsible business landscape that benefits society and the economy in the long run.